Exploring communication strategies for the facilitation of person-centred care: A comparison of three methods for analysis. (18th July 2017) - Forsgren, Emma; Saldert, Charlotta
Abstract : This method study compares the results yielded by using three different methods of examining how communication strategies may facilitate person-centred care in longterm residential care. The analysis involved two quantitative coding systems, which rated language-based and person-centred communication strategies, and a qualitative analysis based on Conversation Analysis. The data consisted of a video-recorded conversation that took place between an enrolled nurse and a resident with dementia in a long-term residential care facility in western Sweden. The qualitative analysis sheds light on several shortcomings in the two quantitative coding systems. Although both coding systems revealed that the enrolled nurse used many facilitating strategies, only one of the systems captured problems in the interaction. The conclusion of this study is that context as well as paralinguistic aspects in communication should be considered in the development and use of quantitative coding systems.